Effects of autoclaving on the proximate composition of stored castor (Ricinus communis) seeds - ANTHONY NEGEDU; JOSEPH B. AMEH; VERONICA J. UMOH; SUNDY E. ATAWODI; MAHENDRA K. RAI (Nusantara Bioscience, 2013)
Abstract. Negedu A, Ameh JB, Umoh VJ, Atawodi SE, Rai MK. 2013. Effects of autoclaving on the proximate composition of stored castor (Ricinus communis) seeds. Nusantara Bioscience 5: 51-56. The effect of autoclaving on the proximate composition, free fatty acids and peroxide value of castor (Ricinus communis L.) seeds in storage were studied. Seeds of castor were surface sterilized, dried and divided into two equal sets of 300g each. One set was autoclaved at 15 1b pressure for 30 minutes at 121oC and the other set served as control. Each set was prepared in triplicates and both sets were stored under same room temperature conditions for a period of 180 days and agitated intermittently. Analysis of the proximate composition showed that autoclaving treatment caused an increased total fat content, reduced moisture, protein, nitrogen-free extract (soluble sugar) and ash contents of the seeds in storage, as well as a non-significant increase in crude fiber (non-soluble sugar) content. It increased the free fatty acid content and decreased the peroxide value of seed oil.